Differences in functional outcomes for adult patients with prosthodontically-treated and -untreated shortened dental arches: a systematic review. - Saadika Khan (Public Library of Science (PLoS), 2014)
Unlabelled This review examined differences in functional outcomes and patient satisfaction when shortened dental arches are left untreated compared to their restoration to complete arch lengths with different prosthodontic interventions. Methods A protocol was developed according to the criteria for a systematic review. All relevant databases were searched to identify appropriate clinical trials regardless of language or publication status. Predetermined eligibility criteria were applied, trial quality assessed and data extracted for each study. Relevant outcomes assessed were: functioning ability, patient satisfaction and harmful effects on oral structures. Results Searches yielded 101 articles: 81 from electronic databases and 20 from reference lists of retrieved articles (PEARLing searches). Sixty-nine citations were assessed for eligibility after removing 32 duplicate records. After reading titles and abstracts, a total of 41 records were excluded and the full-texts of the remaining 28 records were read. Only 21 records were included for the SR because 7 records were excluded after reading the full-text reports. These 21 records report the outcomes of four randomized controlled trials (RCTs) and one non-randomized clinical trial (CT) which were pre-specified and used for this review. No on-going studies were found and no eligible studies were excluded for failure to report the reviewer's pre-specified outcomes. Outcomes were reported in the retrieved 21 articles. A narrative explanation of the pre-specified outcomes is reported for the 3 comparison groups (which were based on the different interventions used for the individual clinical trials). The shortened dental arch as a treatment option is encouraging in terms of functioning, patient satisfaction and cost-effectiveness. By using only high quality studies it was expected that the results would be more reliable when making conclusions and recommendations, but some of the included studies had to be downgraded due to methodological errors.